2017
DOI: 10.1038/srep46403
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Detection and Functional Assessment of Regenerated Nerve after Neural Prosthesis with a PGLA Nerve Conduit

Abstract: This study aimed to observe the morphological characteristics of a PGLA [poly(glycolide-co-L-lactide)] nerve conduit and regenerated nerve bundle in the human body using high-frequency ultrasound and examine functional recovery of the regenerated nerve using functional magnetic resonance imaging (fMRI) after neural prosthesis with a PGLA nerve conduit. Thirty-nine patients underwent high-frequency ultrasound, and one patient with superficial radial nerve injury (27-mm defect) underwent fMRI at one, three, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…28 Preliminary studies showed that serial US can evaluate morphological variations of the regenerated nerve. 29 In particular, the changes to the PN in nerve wrapping and the possibility of following nerve regeneration could theoretically be followed by US, although the morphology of the regenerated PNs do not prove the recovery of nerve function. 29 One additional application could be serial following of the resorption of synthetic conduits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 Preliminary studies showed that serial US can evaluate morphological variations of the regenerated nerve. 29 In particular, the changes to the PN in nerve wrapping and the possibility of following nerve regeneration could theoretically be followed by US, although the morphology of the regenerated PNs do not prove the recovery of nerve function. 29 One additional application could be serial following of the resorption of synthetic conduits.…”
Section: Discussionmentioning
confidence: 99%
“…29 In particular, the changes to the PN in nerve wrapping and the possibility of following nerve regeneration could theoretically be followed by US, although the morphology of the regenerated PNs do not prove the recovery of nerve function. 29 One additional application could be serial following of the resorption of synthetic conduits. In 1 patient, US showed failure of the human umbilical cord artery NC allograft (surgically proved), and the presence of 2 neuromas at the distal and proximal ends of the nerve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of materials have been used in the preparation of magnetic nanofibers, such as chitosan/poly (vinyl alcohol) (PVA), poly (ε-caprolactone) (PCL), hydroxyapatite (HA), magnetic poly (L-lactic acid) (PLLA), poly (D, L-lactic acid) (PDLLA), and poly (glycolide-co-L-lactide) (PGLA) (46)(47)(48)(49)(50). Due to the tunability, porosity, hydrophilicity, capacity for the incorporation of biological factors, and the polymeric nature of hydrogels, they are increasingly used in bone or nerve regeneration, cancer therapy, and tissue engineering (51).…”
Section: Biomaterials Based On Magnetic Fibersmentioning
confidence: 99%
“…Magnetic resonance imaging and ultrasonography, used in clinical practice, can help visualize the peripheral nerve structure in vivo; however, their spatial resolution of hundreds of micrometers is insufficient to visualize cellular structures such as myelinated axons with a diameter of 12–20 µm. [ 11 , 12 , 13 ] Recently, spectral confocal reflectance microscopy [ 14 ] and coherent anti‐Stokes Raman spectroscopy [ 15 ] were successfully applied to visualize the myelinated axons of rodent and rabbit sciatic nerves, respectively, in vivo. However, their narrow field of view (FOV) and nonvolumetric imaging properties provide information limited only to the nerve surface.…”
Section: Introductionmentioning
confidence: 99%